2014
DOI: 10.3892/mmr.2014.2836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiviral therapy on the cellular immune response in patients with chronic hepatitis B

Abstract: Abstract.A weak T-cell immune response to the hepatitis B virus (HBV) is hypothesized to be the primary cause of chronic HBV infection. Emerging evidence suggests that long-term effective antiviral therapy restores the HBV-specific T-cell response from exhaustion. However, the extent to which the cellular immune response can be restored following the persistent suppression of HBV replication by antiviral therapy remains unclear. In order to investigate this question, 46 patients with chronic hepatitis B (CHB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, during last 4 years of the 5 year post-ETV treatment, only IL-4, IL-6 and MIP-1α continued to decrease, while other factors increased to varying degrees. This implies the host immune response varies with the stages of chronic HBV infection and exhibits diverse processes during the antiviral treatment30.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during last 4 years of the 5 year post-ETV treatment, only IL-4, IL-6 and MIP-1α continued to decrease, while other factors increased to varying degrees. This implies the host immune response varies with the stages of chronic HBV infection and exhibits diverse processes during the antiviral treatment30.…”
Section: Discussionmentioning
confidence: 99%
“…al. demonstrated that in CHB patients, antiviral therapy restored these HBV-specific immune responses, and subsequently suppressed HBV replication [30]. However, it is unclear if this immune reconstitution may inadvertently contribute to the progression to HCC in certain individuals due to dysfunctional inflammatory responses causing DNA damage, genomic instability, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Gene type, virus load and immune response function are important factors in HBV infection and chronicity. Therefore, the reduction of immune response function is the main reason of continuous replication of HBV in the body and the increasing viral load ( 4 ). Peripheral blood mononuclear cells (PBMC) play an important role in the process of antiviral immune response, and excessive apoptosis of PBMC after viral infection leads to the reduction of the bodys antiviral immune response function and an increase of virus load ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%